Une expérience de "Mooc professionnel" : des formations numériques à l’Éducation - Olivier Marty (Éducation et Socialisation)
We empirically describe an experimentation of « Professional Mooc » on the French national platform — symptom of digitalization and professionalization of higher education. Henceforth, we analyze this digital training device on three axes: status of professional knowledge, imperfection of educative socialization with this learning tool and, last but not least, the concept of experience to question our experimentation.